A Comparative Study of Generation Z's Working Culture Among Apprentices and Employees in Thai Tourism and Hospitality Organisations: การศึกษาเปรียบเทียบวัฒนธรรมการทำงานของคนเจนเนอเรชั่นซีระหว่างนักศึกษาฝึกงาน และบุคลากรในองค์กรการท่องเที่ยวและการบริการไทย - Nonsiri, Petchsri (Mekong-Salween Civilization Studies Journal, 2025)
This study examined Generation Z's work culture based on their experiences as apprentices and employees within tourism and hospitality organisations, comparing the two groups. The objectives encompassed examining the working culture of Generation Z by self-assessment and to compare perceptions of apprentices and Gen Z employees toward working culture in Tourism and Hospitality organizations of Thailand. The research technique is a quantitative approach with a structured questionnaire to gather data from persons aged 18 to 29, encompassing both apprentices and employees. Cochran’s formula determined the sample size using convenience sampling for infinite populations. The sample comprised 200 employees and 200 apprentices to ensure adequate representation for analysis. Data analysis employing descriptive an independent samples t-test to examine differing perceptions between two sample groups. The findings reveal notable differences in the perceptions of Generation Z working culture between apprentices and Generation Z across fourteen and two attributes of twenty-two assessments, supported by one-way simple t-Test results of p-value less than < 0.001 and 0.05 respectively. The study recommends various strategies to attract and retain Generation Z in Human Resource Management, including Personalized Training, Incorporating Social Responsibility and Flexible Workplace Environment.